A comparative analysis of biometric parameters of optic nerves obtained by ultrasonic sensors of varied frequencies - V. V. Neroev; T. N. Kiseleva; M. S. Zaytsev; A. V. Baeva; E. K. Eliseeva; A. I. Ushakov (Российский офтальмологический журнал)
Purpose: a comparative analysis of biometric parameters of the optic nerve obtained by different diagnostic ultrasound sensors.Material and methods. We examined 20 healthy volunteers with emmetropia aged 20 to 40 years (40 eyes), average age 30.5 ± 5.4 years, who had no complaints or ophthalmic pathologies. Ultrasound scanning was performed on a multifunctional Voluson E8 (GE) scanner (11–18 MHz linear sensor), ophthalmic ultrasound device Ellex Eyecubed (a conventional 10 MHz transducer) and an ophthalmic scanner Absolu «Quantel Medical» (a 20 MHz transducer). All examinations were carried out by one operator who used the same scanning technique and measured the optic nerve sheath diameter (ONSD) and optic nerve diameter (OND) without sheaths in both eyes. Six consequent measurements of the ONSD and the OND parameters were performed to ascertain the reproducibility of the examinations and evaluate the variation coefficient.Results. The analysis revealed no statistically significant differences in the ONSD and in the OND obtained with 11–18 MHz, 10 MHz and 20 MHz transducers in the B-mode (р > 0.05). The minimum variation coefficient of the optic nerve thickness parameters was registered using a high-frequency 20 MHz transducer on the ophthalmic scanner. The biometry obtained with a high frequency 20 MHz transducer could be considered as the most reproducible.Conclusion. A high frequency 20 MHz transducer can be recommended for optimal visualization and precise evaluation of biometric parameters of the retrobulbar part of the optic nerve. Transducers of multifunctional scanners with the frequency range from 11 to 20 MHz can be used for measurements of the optic nerve sheath diameter.